Failure To Thrive In Children Under Two Years Of Age And Associated Factors, A Hospital- Based Study - Hassan M Khalil; Sundus M Husain; Maghreb S Alkhateeb; Jalil I Alezzi (Diyala Journal of Medicine, 2019)
Background: Failure to thrive is a common problem in infancy and children result from inadequate nutrition or chronic illnesses.